Eyimofe (this is my desire) [videorecording (DVD)] - Akuwudike, Jude; Edun, Tomiwa; Ami-Williams, Temi; Ebijie, Cynthia; Alexander, Jacob (Criterion collection, 2022)
"This revelatory, award-winning debut feature from co-directors (and twin brothers) Arie and Chuko Esiri is a heartrending and hopeful portrait of everyday human endurance in Lagos, Nigeria. Shot on richly textured 16 mm film and infused with the spirit of neorealism, Eyimofe (This Is My Dream) traces the journeys of two distantly connected strangers--Mofe (Jude Akuwudike), an electrician dealing with the fallout of a family tragedy, and Rosa (Temi Ami-Williams), a hairdresser supporting her pregnant teenage sister as they each pursue their dream of starting a new life in Europe while bumping up against the harsh economic realities of a world in which every interaction is a transaction. From these intimate stories emerges a vivid snapshot of life in contemporary Lagos, whose social fabric is captured in all its vibrancy and complexity"--Container.